AAV-mediated transduction of songbird retina - Seth, Pranav Kumar; Heyers, Dominik; Satish, Baladev; Mendoza, Ezequiel; Haase, Katrin; Borowsky, Lisa; Musielak, Isabelle; Koch, Karl-Wilhelm; Feederle, Regina; Scharff, Constance; Dedek, Karin; Mouritsen, Henrik (Frontiers in Physiology, 2025)
IntroductionGenetic manipulation of murine retinal tissue through ocular administration of adeno-associated viruses (AAVs) has become a standard technique to investigate a multitude of mechanisms underlying retinal physiology. Resultantly, developments of recombinant viral vectors with improved transduction efficiency and further methodological improvements have mostly focused on murine tissue, whereas AAVs successfully targeting avian retinae have remained scarce.MethodologyUsing a custom-designed injection setup, we identified a viral serotype with the capability to successfully induce widespread transduction of the bird retina.ResultsIntravitreal administration of an AAV type 2/9 encoding for enhanced green fluorescent protein (EGFP) in night-migratory European robins (Erithacus rubecula) resulted in transduction coverages of up to 60% within retinal tissue. Subsequent immunohistochemical analyses revealed that the AAV2/9-EGFP serotype almost exclusively targeted photoreceptors: rods, various single cones (UV, blue, green, and red cones), and both (accessory and principal) members of double cones.DiscussionThe consistently high and photoreceptor-specific transduction efficiency makes the AAV2/9 serotype a powerful tool for carrying out genetic manipulations in avian retinal photoreceptors, thus opening a wealth of opportunities to investigate physiological aspects underlying retinal processing in birds, such as physiological recordings and/or post-transductional behavioural readouts for future vision-related research.